Analisis Pasar Perancangan Website Geographical Information System Potensi Bisnis Perikanan Tangkap Jatim - Anisyah Tri Milenia; Ristanti Akseptori; R.A. Norromadani Yuniati (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2022)
GIS Cluster of Fisheries Business Strategy for East Java is a visual map design based on the Geographical Information System (GIS) website that presents the potential and business strategies to capture fisheries in East Java Province. Market analysis is used to assess the feasibility of market aspects using the dimensions of market potential, competitors, segmentation targeting and positioning, interests for business actors, income and business model canvas. The research methodology was descriptive qualitative using primary and secondary data. The results obtained from the market aspect with an overall average score on 3 dimensions indicated that respondents tend to agree that GIS design will have a positive impact on business actors. The East Java Fisheries Business Strategy Cluster GIS had a positioning, which was a superior feature by grouping information and data to find out the capture fisheries business strategy. Based on the results of the market analysis on the GIS system, it was said to be feasible in terms of each dimension.